Paradoxical attitudes toward premarital dating and sexual encounters in Tehran, Iran: a cross-sectional study. Issue 1 (December 2016) - Motamedi, Mahnaz; Merghati-Khoei, Effat; Shahbazi, Mohammad; Rahimi-Naghani, Shahrzad; Salehi, Mehrdad; Karimi, Mehrdad; Hajebi, Ahmad; Khalajabadi-Farahani, Farideh
Abstract Background The purpose of this study is to assess attitudes toward premarital dating and sexual encounters in individuals aged 15–49 years in Tehran. Methods Utilizing the attitudes section of an original cross-sectional study (n  = 755) aimed at assessing sexual health needs of adults, this paper examined personal attitudes towards premarital dating, non-sexual relationships and sexual encounters in both male and female adults aged between 15–49 years. Multi-stage cluster random sampling and a validated/reliable questionnaire were used. Descriptive, bivariate and multivariate analyses were conducted using statistical software. Results The results indicated that the majority of the participants were supportive of dating. Almost three-fourths of the males were more positively inclined towards non-sexual, yet tactile, affectionate interactions between unmarried males and females as opposed to only half of the females (70 % vs. 50.5 %). Also, males held significantly more liberal attitudes than females in their acceptance of premarital sex. On preserving virginity prior to marriage, 43 % of the males felt that it was important for a female to be a virgin, whereas only 26 % felt it was important for males to remain a virgin. Interestingly, more females (61 %) supported the importance of a female's virginity compared with the importance of males' virginity (48 %). This study showed that, being a male, of a younger age, single, and being less religious or being secular were important determinants of a liberal sexual attitude. Conclusion These results might reflect a socio-cultural transition in the sexual attitudes of different age groups of participants - a phenomenon that will need empirical studies to unpack in the Iranian socio-cultural context.